Banzato, Guillermo (ed.) (2013), Tierras rurales. Políticas, transacciones y mercados en Argentina, 1780-1914, Rosario, Prohistoria ediciones, 242 p. ISBN 978-987-1855-38-4 - Artaza, Sebastián Ignacio (2014)
Fil: Artaza, Sebastián Ignacio. Universidad Nacional Tres de Febrero